Micro- and Nanoplastics as Environmental Stressors: Mechanistic Links Among Gut Dysbiosis, Inflammation, and Systemic Health Effects - Guilherme de Oliveira Ferreira; Maria Júlia Ferreira Alves; Priscila Oliveira de Paula Charret; Thaysi Rodrigues; Natália A. Borges; Ludmila F. M. F. Cardozo; Denise Mafra (Journal of Xenobiotics, 2026)
Microplastics and nanoplastics (MNPs) have emerged as widespread environmental contaminants, with increasing evidence suggesting that chronic exposure may adversely affect human health. Experimental and emerging human studies indicate that MNPs can interact with multiple biological systems and trigger a range of mechanisms, including oxidative stress, mitochondrial dysfunction, cellular injury, barrier disruption, and immune and inflammatory responses. These effects may involve direct interactions with tissues and cells as well as indirect pathways, including alterations in gut microbial and intestinal homeostasis. In turn, persistent inflammatory and metabolic disturbances may contribute to tissue dysfunction and the development or progression of chronic diseases. This narrative review summarizes current evidence on the biological effects of MNP exposure, focusing on the mechanisms linking environmental exposure to chronic inflammation and disease. We discuss their potential involvement in cardiovascular, liver, kidney, respiratory, and neurological diseases, while highlighting the emerging role of the gut microbiota and intestinal barrier as potential modulators of these effects. Given the limitations of current human evidence and the heterogeneity of experimental models, we also discuss major knowledge gaps and the need for further mechanistic and epidemiological studies to clarify the clinical relevance of chronic MNPs exposure.